Misattribution of self-generated speech in relation to hallucinatory proneness and delusional ideation in healthy volunteers. - Allen, P; Freeman, D; Johns, L; McGuire, P (2006)
When patients with hallucinations and delusions encounter their own distorted speech they tend to mistakenly attribute it to someone else. This external misattribution of self-generated material is thought to be associated with 'positive' psychotic symptoms. The aim of the present study was to examine this process in relation to the predisposition to hallucination-like experiences and unusual beliefs in a healthy population. Fifty-seven volunteers completed assessments of hallucination proneness and delusional ideation and performed a source-monitoring task. Participants listened to a series of pre-recorded words for which the source (self/non-self) and acoustic quality (undistorted/distorted) of the speech were varied across trials. Participants indicated whether the words were spoken in their own or another person's voice via a button press. Misattribution errors were greatest when participants made source judgements about their own distorted speech (p < 0.01) and were positively correlated with delusional ideation scores, particularly the level of conviction with which delusional ideas were held (p = 0.03), and there was a trend for a positive correlation with hallucination proneness scores. There was a negative correlation between unsure responses and delusional ideation when participants were processing their own distorted speech (p = -0.03). The misattribution of self-generated speech occurs in healthy individuals with high levels of psychotic-like experiences. This suggests that the same cognitive impairments may underlie psychotic phenomena in healthy individuals as in patients with psychotic disorders, consistent with a continuum model of psychosis.